Male Sexual Abuse - Dabas, Mansi (Trinity Law Review, 2021)
Whenever we talk about sexual assault/harassment, it is generally another women being assaulted. The only concern lies with women and no other gender specifically. Norms, society, principles, statistics states that more of women in need, if we compare the information related harassments it will always be women. The only possible assumption about not being much concerned about men is the world has still not accepted that something this can happen to a male. A lot of comparisons are made but no recent studies are found as an accurate proof, especially in country like India. This study confirms that a male sexual abuse is a prevalent problem. It is also evident that victimized men were depressed and yet do not seek health services. Efforts should make to reach men with a history of sexual assault.